2019
DOI: 10.1101/820886
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TRIM34 acts with TRIM5 to restrict HIV and SIV capsids

Abstract: 1The HIV-1 capsid protein makes up the core of the virion and plays a critical role in early 2 steps of HIV replication. Due to its exposure in the cytoplasm after entry, HIV capsid is a 3 target for host cell factors that act directly to block infection such as TRIM5 and MxB. 4 Several host proteins also play a role in facilitating infection, including in the protection 5 of HIV-1 capsid from recognition by host cell restriction factors. Through an unbiased 6 screening approach, called HIV-CRISPR, we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…It has recently been reported that SARS-CoV-2 can cause acute pulmonary epithelial senescence and subsequent fibrosis, although the exact mechanism is not yet understood (Hong et al, 2022). TRIM34, up-regulated in our study, has been shown to play a role in the restriction of HIV-1 infection and programmed cell death activated by IAV (Ohainle et al, 2019; Wang et al, 2022). HIV-1-induced immune dysfunction has also been linked to early SARS-CoV-2 clearance (Zhao et al, 2020).…”
Section: Discussionmentioning
confidence: 50%
“…It has recently been reported that SARS-CoV-2 can cause acute pulmonary epithelial senescence and subsequent fibrosis, although the exact mechanism is not yet understood (Hong et al, 2022). TRIM34, up-regulated in our study, has been shown to play a role in the restriction of HIV-1 infection and programmed cell death activated by IAV (Ohainle et al, 2019; Wang et al, 2022). HIV-1-induced immune dysfunction has also been linked to early SARS-CoV-2 clearance (Zhao et al, 2020).…”
Section: Discussionmentioning
confidence: 50%